FORMULASI CRISPY COOKIES BERBAHAN BAKU TEPUNG KACANG KORO PEDANG (Canavalia ensiformis) TERMODIFIKASI - intan kusumaningrum kusumaningrum (Universitas Djuanda, 2018)
This research was conducted to obtain the influence between the comparison of modified jack bean flour with cornstarch (100:0, 90:10, 80:10, 70:30, 60:40, and 50:50) in crispy cookies formulation to obtain the selected formulation sensory values of the product which examined by professional panelists and to analyze the nutritional values of the product. This research was divided into two stages : preparation and main research. Preparation stage consists of making modified jack bean flour. Main research stage consists of (1) Producing crispy cookies, (2) Organoleptic testing by Qualitative Descriptive Analysis method, (3) Physical testing (crispness), (4) Data analysis and (5) Chemical analysis for the selected formula. The results showed that the cookies produced from jack bean flour still have undesirable sensoric characters such as unpleasant aroma; bitter and sour taste; bitter, sour, and beany after taste. The selected formula was the formula with the comparison of modified jack bean flour : cornstarch = 60:40. The chemical analysis results of the selected formula were: water content of 1,34%, ash content of 2,14%, protein value of 14,33%, fat of 30,30% ,fibre of 0,30%, carbohydrate of 51,89%, and HCN of 0.01%.